Mechanical and corrosion behaviour of copper matrix composites fabricated by powder metallurgy process. (2020) - Mohanavel, V.; Vinoth, T.; Iyankumar, R.; Vinoth, N.
Abstract: The composite technology is a gate way of invention of new materials with desirable properties. Synthesize of Copper Metal Matrix Composite (CMMC) is focused in this paper. The copper is reinforced with tungsten carbide and groundnut shell ash. The composite matrix of 80% of copper powder (Cu), 15% Tungsten Carbide Powder (WC) and 5% of Ash of Groundnut shell (GSA) preferred in which copper is matrix material. The composite manufactured by powder metallurgy technology. The proposed composite investigated by microscopy analysis, corrosive analysis and hardness analysis. The reinforcement of proposed proportion of 15% Tungsten Carbide Powder and 5% of Ash of Groundnut shell, improved hardness and reduced corrosion rate (increased corrosive resistance). The Scanning Electron Microscopy image ensures uniform distribution of reinforced particles in the matrix material. The control specimen made with only copper powder by same method of manufacturing and testing also to expose the effects of reinforcement.